1995
DOI: 10.1073/pnas.92.21.9851
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of high-avidity T cells by thymic epithelium.

Abstract: Tolerance induction by thymic epithelium induces a state of so-called "split tolerance," characterized in vivo by tolerance and in vitro by reactivity to a given thymically expressed antigen. Using a model major histocompatibility complex class I antigen, H-2Kb (Kb), three mechanisms of thymic epithelium-induced tolerance were tested: induction of tolerance of tissue-specific antigens exclusively, selective inactivation of T helper cell-independent cytotoxic T lymphocytes, and deletion of high-avidity T cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(28 citation statements)
references
References 25 publications
2
23
1
2
Order By: Relevance
“…There was nearly a 100-fold difference in their ability to produce IFN-␥ after stimulation with subsaturating levels of peptide Ag. This confirms our previous observations noting large differences in the peptide requirements for inducing CTL activity by these low-avidity and high-avidity T cell populations (9,10), which is consistent with the avidity model for thymic negative selection (2). To further assess these differences, we performed functional fingerprinting analysis using altered peptide ligands for stimulation (Fig.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…There was nearly a 100-fold difference in their ability to produce IFN-␥ after stimulation with subsaturating levels of peptide Ag. This confirms our previous observations noting large differences in the peptide requirements for inducing CTL activity by these low-avidity and high-avidity T cell populations (9,10), which is consistent with the avidity model for thymic negative selection (2). To further assess these differences, we performed functional fingerprinting analysis using altered peptide ligands for stimulation (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…N egative selection is a unique process that determines which T cells will be deleted in the thymus and which ones will differentiate into mature cells that are then released into the periphery (1)(2)(3)(4)(5). Positive selection occurs first and requires that T cells demonstrate at least a weak interaction with self-peptides presented by the appropriate MHC molecules (6,7).…”
Section: Preferential Escape Of Subdominant Cd8 ؉ T Cells During Negamentioning
confidence: 99%
“…However, ample evidence exists that medullary epithelial cells are capable to delete or anergize self-reactive T cells (52,54,68). Here we have demonstrated that Aire expression 1) correlates with the correct structural organization of the thymic microenvironment, 2) is localized to cells and anatomical sites known to effect negative selection, and 3) is modulated by thymocytes undergoing negative selection.…”
Section: Discussionmentioning
confidence: 73%
“…T cells capable of responding to their antigen in vitro can be tolerant to the same antigen in vivo (33)(34)(35). To address this possibility, G206 mice were immunized with p206 in incomplete Freund's adjuvant (IFA), and ex vivo T cell proliferation assays were performed 5 days later with draining lymph node cells.…”
Section: Antigen-specific Proliferation and Cytokine Production By G2mentioning
confidence: 99%